2021
DOI: 10.1097/mao.0000000000003089
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Characteristics of Sigmoid Sinus Wall Anomalies, Idiopathic Intracranial Hypertension, and Spontaneous CSF Leaks

Abstract: Objective:To assess the frequency of radiographic features of elevated intracranial pressure (ICP) in patients with sigmoid sinus wall anomalies (SSWA) and compare to those in idiopathic intracranial hypertension (IIH) and spontaneous CSF (sCSF) leaks.Study Design:Retrospective review.Setting:Tertiary care center.Patients:110 patients - 62 SSWAs, 19 IIH, 29 sCSF leaks.Main Outcome Measures:Demographics, comorbidities and radiographic features by diagnosis.Results:Imaging findings indicative of elevated ICP wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This may be due to the regulation of flow dynamics via the external jugular and vertebral pathways. Although it is highly possible that some degree of flow anomaly/increase in intracranial pressure promotes osteolytic effects, 19,20 increased cerebrospinal opening pressure is not a definitive finding in patients with PT associated with SSWAs. 28 Except for neuro-ophthalmologic signs or symptoms of IIH, neuroimaging findings are not required for the diagnosis of definite IIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the regulation of flow dynamics via the external jugular and vertebral pathways. Although it is highly possible that some degree of flow anomaly/increase in intracranial pressure promotes osteolytic effects, 19,20 increased cerebrospinal opening pressure is not a definitive finding in patients with PT associated with SSWAs. 28 Except for neuro-ophthalmologic signs or symptoms of IIH, neuroimaging findings are not required for the diagnosis of definite IIH.…”
Section: Discussionmentioning
confidence: 99%
“…7 Researchers have also suggested that spontaneous cerebrospinal fluid leakage can occur in the late stage of SSWA development if increases in intracranial pressure remain unresolved. 19 Furthermore, a recent study provided striking evidence suggesting that addressing flow pathologies can reverse the process of SSWA formation. 20 SSWAs may therefore represent anatomical abnormalities that develop due to pathologic accumulation of flow perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some patients may have IIH without papilledema, exhibiting a moderate increase in intracranial pressure. Further investigation is required to elucidate the true cause of skull base erosion, such as SSWAs and spontaneous cerebrospinal fluid leak, among others (40). Lastly, qualitative methods for analyzing the thickness of the vascular wall and dura over SSWAs are limited.…”
Section: Discussionmentioning
confidence: 99%
“…SSWAs include sigmoid sinus diverticulum (SSD) and wall dehiscence, both of which are believed to result from distal TS stenosis and elevated intracranial pressure commonly observed in individuals with idiopathic intracranial hypertension (IIH) (4). However, while TS stenosis is a common finding in the normal population, SSWAs are comparatively rare, making them more likely to be associated with PT generation (5).…”
Section: Introductionmentioning
confidence: 99%